EDUCATING PRESCHOOLERS IN THE SPIRIT OF NATIONAL TRADITIONS AND NATIONAL VALUES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the pedagogical foundations of educating preschool children in the spirit of national customs and traditions, forming a sense of compassion.